Pemilihan Umum 1955 di Sulawesi Selatan: Studi Kasus Afdeeling Parepare - Irdaniah Irdaniah; Andi Ima Kusuma; Muhammad Rasyid Ridha (Universitas Negeri Makassar, 2022)
This study aims to determine: (1) to find out the situation of South Sulawesi, especially the Afdeeling Parepare region before the general election, (2) to understand the process of preparing for the 1955 general election until its implementation. This research uses qualitative research with a historical approach, namely heuristics, criticism, interpretation and historiography. Based on the data sources used, namely primary data and secondary data. Primary data was obtained through archival documents found at the Office of the Archives and Library of South Sulawesi Province. While secondary data is data obtained from various literatures such as books, journals, theses, theses and other sources related to the research theme. Management of data presentation is done using historical research methods. The results showed that: (1) the situation in South Sulawesi ahead of the 1955 general election, especially in the Afdeeling Parepare area, could be categorized as less safe. This was due to the disturbance of the DI/TII gang who tried to thwart the general election. This disturbance hinders general election preparations from registration of general election participants to the implementation of general elections. (2) the general election in Parepare succeeded in voting on September 29, 1955. The results of the general election in Parepare were five parties that received the most votes, namely: Masyumi, PSII, PKR, NU and PNI.